Cancer-microenvironment triggered self-assembling therapy with molecular blocks. Issue 4 (1st February 2021) - Nakatsuji, Hirotaka; Shioji, Yudai; Hiraoka, Noboru; Okada, Yuta; Kato, Natsuko; Shibata, Sayaka; Aoki, Ichio; Matsusaki, Michiya
Abstract : Molecular blocks (4-MB) were designed to circulate as a single molecule or as a few molecules in blood vessels and self-assemble in response to a tumor specific conditions, as a cancer therapeutic agent. Abstract : Drug delivery systems (DDS) have been studied in an effort to reduce side effects by increasing the accumulation of anticancer drugs in cancer cells. However, the transport efficiency is still low due to the blocking by surrounding stromal tissues and the multiple intracellular drug transportation processes required to get the drug to a target cytosol. Thus, improving the efficiency of cancer therapy is still a major challenge. Here, a drug-free cancer microenvironment-targeting therapy using molecular blocks (MBs) is demonstrated, which is designed for efficient blood circulation and penetration through the stromal tissues as either a single molecule or a few molecules. When the MBs moved to a cancer microenvironment by the enhanced permeability and retention effect, they formed a self-assembled aggregate on the cancer cell surfaces in response to the weak acid (pH ∼ 6.5) condition leading to subsequent cancer cell death by membrane disruption. This strategy avoids multiple intracellular transportation processes and also stimulates cell membrane disruption by self-assembly of the MB via hydrophobic interactions. Deoxycholic acid (DCA) was selected as a cancer microenvironment-responsive unit because its p K a = 6.6. The DCA conjugated 4-arm poly(ethylene glycol) (4-MB) showed self-assembly phenomena on cancer cell membranes and subsequently significant cytotoxicity was clearly observed. Moreover, they clearly showed efficient accumulation in the tumor and the effective suppression of tumor growth in in vivo experiments. This MB therapy will be a new strategy for addressing the current issues of DDS.